Synthesis and characterization of heterocyclic chalcones containing halogenated thiophenes - Al-Maqtari, Helmi Mohammed (Penerbit UTM Press, 2015)
Heterocyclic chalcones containing halogenated thiophenes were synthesized. The first step was to synthesize 3-acetyl-2,5-dichlorothiophene and 2-acetyl-5-chlorothiophene as heterocyclic ketones by using Friedel-Crafts acylation. The ketones were then used to synthesize thiophene chalcones through Claisen-Schmidt reaction with the respective heterocyclic aldehydes such as 5-bromothiophene-2-carbaldehyde, 3-methyl-2-thiophene carboxaldehyde and 2-thiophene carboxaldehyde with 3-acetyl-2,5-dichlorothiophene or 2-acetyl-5-chlorothiophene in presence of basic medium, sodium hydroxide to form the corresponding chalcones. Structures of the synthetic compounds were confirmed by IR, MS, 1H and 13C NMR spectral data.